THE RESEARCH OF WORK MOTIVATION AS A MECHANISM TO IMPROVE THE PERSONNEL POLICY OF PUBLIC SERVANTS OF THE FEDERAL BAILIFF SERVICE - Irina Novikova (Вестник Северо-Кавказского федерального университета)
Nowadays, the most pressing task is study of reasons to low motivation of the bailiffs in their performance as well as the development of measures to improve the personnel policy ofthe Public Servants of the Federal Bailiff Service. In pursuance of this objective, the sociological research has been held by authors in structural units of Federal Bailiff Service of the Stavropol region in January-February 2016 on the basis of North-Caucasus Federal University. Sociological researches are led in the questionnaire form and in-depth interviews. The survey objectives were the following: assessment of bailiffs working environment; determination of the relationship between the remuneration of bailiffs and the results of their work; revealing interrelation between the bailiff class rate and remuneration; impact assessment of operating results and bailiffs 'skills upgrading on career growth. Results management of the quantitative researches was performed using the counting program VORTEX 8.0. These methods were aimed to study motivation of bailiffs in their activities, and the subsequent development of measures to improve the personnel policy of the Public Servants of the Federal Bailiff Service. These data revealed the necessity to develop the material incentive system of the Public Servants of the Federal Bailiff Service, and also identified several areas for improving legal and regulatoryframework in this area.